A 8-Year-Forgotten Ureteral Stent after Kidney Transplantation: Treatment and Long-term Follow-up. Issue 1 (January 2013) - Lasaponara, Fedele; Dalmasso, Ettore; Santià, Silvia; Sedigh, Omidreza; Bosio, Andrea; Pasquale, Giovanni; Segoloni, Giuseppe P.; Fontana, Dario
Introduction: Forgotten indwelling ureteral stents can cause significant urological complications. Only few cases are reported after kindney transplantation. Materials and Methods: We present a case of a 39-year-old woman, transplanted in 1993 and referred to our Transplant Center 8 years later, because of a serious urinary tract infection with renal function impairment. Abdominal CT scan showed pyelonephritis and hydronephrosis in the transplanted kidney and the presence of a calcific ureteral stent, which had been forgotten in situ for 8 years. The stent was removed, but it was impossibile to replace it with a new stent both retrogradely and anterogradely, because of a tight obstruction of the mid ureter. So a uretero-ureteral anastomosis with up urinary tract was performed. Results: No intra- or post-operative complications occurred. At 9 years' follow-up, the patient shows an optimal renal function, with no urinary tract infection. Discussion: A forgotten ureteral stent in a trasplanted kidney can cause a lot of complications and can lead to graft loss. The prosthesis may cause an irreversibile ureteral damage, so, as in our experience, forgetting a ureteral stent can result in a complex surgery.